CFTR gene variants, air pollution, and childhood asthma in a California Medicaid population. Issue 11 (17th August 2022) - Thilakaratne, Ruwan; Graham, Steve; Moua, John; Jones, Caitlin G.; Collins, Caroline; Mann, Jennifer; Sciortino, Stanley; Wong, Jacklyn; Kharrazi, Martin
Abstract: Carriers of the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene ("carriers") have been found to have an increased risk of persistent asthma. However, it is unclear at what level of CFTR function this risk exists and whether it is modified by asthmogens, such as air pollution. We conducted a retrospective cohort study of children born in California between July 2007 and December 2013, linking CFTR genotype data from the California newborn screening program to Medicaid claims records through March 17, 2020 to identify asthma cases, and to air pollution data from CalEnviroScreen 3.0 to identify levels of particulate matter with diameter 2.5 microns or smaller (PM2.5 ). Log‐binomial regression models for asthma risk were fitted, adjusting for race/ethnicity and sex. Compared to population controls, carriers had higher risk of asthma (adjusted risk ratio (aRR) = 1.29, 95% confidence interval (CI): 0.98, 1.69; p  < 0.1). Other non‐CF‐causing variants on the second allele did not appear to further increase risk. Genotypes with the greatest asthma risk were F508del with an intron 10 T7 or (TG)11T5 in trans (aRR=1.52, 95% CI: 1.10, 2.12). This association was higher among children living in areas at or above (aRR = 1.80) versus below (aRR = 1.37) the current national air quality standard for PM2.5, though this difference was not statistically significant ( p interaction  > 0.2). These results suggest carriers with CFTR functional levels between 25% and 45% of wildtype are at increased risk of asthma. Knowledge of CFTR genotype in asthmatics may be important to open new CFTR‐related treatment options for these patients.